Current Trends in The Formation of Mathematical Terminology on An Online Platform - Jumabek, Seypullaev; Tuwelbay, Kurbanbaev; Allabay, Arziev; Geldibayev, Begench (SOTVI, 2024)
To monitor quality improvement and student learning outcomes, schools must adopt a Minimum Competency Assessment (MCA). The Minimal Competence Assessment consists of two sub-tests: literacy and numeracy. This is in accordance with the provisions of the Indonesian Ministry of Education, Culture, Research and Technology in order to improve the quality of learning and student learning outcomes. The existing test method has limits with school resources that cannot satisfy the quota of pupils who can utilize the program jointly. In addition, the existing system is incapable of displaying student grades because the evaluation is a cumulative score for the whole student body. Hence, the school constructed a web service-based application utilizing the Representational State Transfer approaches so that it could independently administer complete numeracy and literacy assessments to its pupils, allowing schools to track their students' numeracy and literacy improvement. The system is constructed utilizing two distinct platforms, namely web-based apps and mobile applications based on Android. Web-based application was developed for admin and teachers while mobile application was developed for students. The findings of this study's testing indicated that the web service application performed as predicted. According to the findings of the questionnaires given to evaluate the application's usability using the Nielsen technique, teachers were happy with the application's Learnability, Memorability, Efficiency, Errors, and Satisfaction. The majority of instructors are satisfied with the implementation of this Minimum Competence Application, according to the survey findings.